2022
DOI: 10.2147/ijgm.s357097
|View full text |Cite
|
Sign up to set email alerts
|

Admission Levels of Serum P-Selectin and IL-6 Can Predict Development of Deep Venous Thrombosis in Hospitalized Covid-19 Patients

Abstract: Background and Aim Deep venous thrombosis (DVT) of the lower extremities is common in Covid-19 patients. Interleukin (IL)-6 and P-selectin were found to be elevated in Covid-19 patients. The current study aimed to evaluate P-selectin and IL6 in Covid-19 patients with DVT and to explore its relation to clinical and laboratory parameters in those patients. Patients and methods The present retrospective study included 150 hospitalized COVID-19 patients diagnosed on the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…showed higher P‐selectin levels in severe COVID‐19 patients and non‐survivors and stated that P‐selectin concentrations increases with disease severity 36 . Several studies have related high levels of P‐selectin to hypercoagulopathy observed in COVID‐19 patients 10,11,77 . Fenyves et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…showed higher P‐selectin levels in severe COVID‐19 patients and non‐survivors and stated that P‐selectin concentrations increases with disease severity 36 . Several studies have related high levels of P‐selectin to hypercoagulopathy observed in COVID‐19 patients 10,11,77 . Fenyves et al.…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies 9,11,29,41,45,[71][72][73][74][75] for E-selectin and 11 studies for Pselectin 10,11,32,36,45,52,71,72,[76][77][78] were reviewed with a total of 896 (351 with poor outcome vs. 545 with good outcome) and 1042 patients (353 with poor outcome vs. 689 with good outcome) for Eselectin and P-selectin respectively. The pooled standard mean difference among the two groups showed a significant increase in Eselectin and P-selectin levels among patients with poor outcome relative to those with good outcome (SMD: 1.09 (0.55, 1.63), p < 0.0001 for E-selectin and SMD: 0.59 (0.24, 0.94), p = 0.001 for Pselectin) (Figure 5, panel A and B respectively).…”
Section: E-selectin and P-selectinmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relationships between thrombosis and IL6 and CRP, which were included in the score, have been previously explored. For instance, Farouk et al reported that IL6 levels at admission were related to DVT [ 19 ]. Similarly, Smilowitz found that the association between CRP levels and adverse outcomes was consistent in patients with low and high D-dimer levels [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective multicenter cohort study including 1240 hospitalized COVID-19 patients who performed a CT pulmonary angiography, only 11.7% of 103 patients diagnosed with pulmonary thrombosis had DVT [ 157 ]. DVT was found in 59 patients (39.3%) when Doppler ultrasound was used systematically for evaluation of the lower extremities during hospital admission for COVID-19 patients [ 158 ]. In another study, none of the patients with pulmonary thrombosis had clinical evidence of DVT [ 152 ].…”
Section: The Role Of Venous Thromboembolismmentioning
confidence: 99%